Activin A is an anticatabolic autocrine cytokine in articular cartilage whose production is controlled by fibroblast growth factor 2 and NF-kappaB. - Alexander, S; Watt, F; Sawaji, Y; Hermansson, M; Saklatvala, J (2007)
OBJECTIVE: Proteomic analysis has previously shown that activin A, a member of the transforming growth factor beta family, is produced by human articular cartilage. This study was undertaken to investigate whether activin A affects cartilage matrix catabolism and how its production is regulated. METHODS: The effect of exogenous activin A on interleukin-1-induced aggrecanase-generated neoepitope production was assessed by Western blotting, using medium from human cartilage explants. Levels of activin A production were determined by enzyme-linked immunosorbent assay. For genes of interest, messenger RNA (mRNA) induction in cartilage explants or primary chondrocyte monolayers was assessed by reverse transcriptase-polymerase chain reaction. Activin A activity in cartilage explant medium was measured by incubating it with human dermal fibroblasts and determining the increase in phospho-Smad2 by Western blotting. RESULTS: Activin A (1-10 ng/ml) suppressed aggrecanase-mediated cleavage of aggrecan in human articular cartilage. Activin A mRNA and protein secretion were induced by dissection and culture of human or porcine articular cartilage. This activin A was biologically active. Its production was due to an active cellular process and was enhanced in osteoarthritic (OA) tissue. Activin A production on dissection was reduced by 80% by the fibroblast growth factor (FGF) receptor inhibitor PD173074 and by 70% by the IKK inhibitor BMS345541. CONCLUSION: Activin A is potentially an anticatabolic molecule in articular cartilage. Its expression is induced by wounding in an FGF-2- and NF-kappaB-dependent manner. OA cartilage produced more activin A than did normal cartilage in vitro.